2021
DOI: 10.3390/su131810005
|View full text |Cite
|
Sign up to set email alerts
|

Research on Environmental Regulation, Technological Innovation and Green Transformation of Manufacturing Industry in the Yangtze River Economic Belt

Abstract: The green transformation of the manufacturing industry is crucial for high-quality development of the Yangtze River Economic Belt, and environmental regulation and technological innovation may play key roles. Considering the undesirable output of the manufacturing industry, this paper adopted the undesirable-SE-SBM Model to measure the green transformation efficiency, which can reflect the core transformation performance. On this basis, this paper respectively adopted system generalized method of moments (SYS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 86 publications
0
19
0
Order By: Relevance
“…For every 1% decrease in energy consumption per unit of GDP, green development efficiency increases by 0.1401%; therefore, only by improving energy utilization and vigorously promoting the use of clean energy can green development efficiency be improved. The finding of a significant inhibitory effect of external openings on green development efficiency demonstrates the existence of the pollution paradise hypothesis [ 59 ], which indicates that most of the foreign-funded enterprises introduced by the municipalities in the Yangtze River Economic Belt are polluting and have caused irreversible damage to the ecological environment.…”
Section: Resultsmentioning
confidence: 99%
“…For every 1% decrease in energy consumption per unit of GDP, green development efficiency increases by 0.1401%; therefore, only by improving energy utilization and vigorously promoting the use of clean energy can green development efficiency be improved. The finding of a significant inhibitory effect of external openings on green development efficiency demonstrates the existence of the pollution paradise hypothesis [ 59 ], which indicates that most of the foreign-funded enterprises introduced by the municipalities in the Yangtze River Economic Belt are polluting and have caused irreversible damage to the ecological environment.…”
Section: Resultsmentioning
confidence: 99%
“…It may be that the Chinese government promotes the transfer of industries to the west and central, including both high-tech industries and traditional manufacturing industries such as building materials and chemicals. The transfer of industries is accompanied by the transfer of pollution, which leads to a gradual increase in MCI from east to west (Zhao et al 2021 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The driving factors of green transition are technological innovation, industrial structure, energy structure, foreign trade level, etc. Zhao et al (2021) found that technological innovation can improve production methods, increase the output level and promote energy conservation and emission reduction, while scientific research investment has not brought the corresponding improvement of technological innovation. Therefore, larger-scale promotion of low-carbon technologies, elimination of outdated production capacity, and reduction of excess capacity are critical to green development (Li and Lin, 2016).…”
Section: The Evaluation and Drives Of Manufacturing Industry Green Tr...mentioning
confidence: 99%